The Effects of Sesamin Supplementation on Obesity, Blood Pressure, and Lipid Profile: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Sun, Yiting; Ren, Jingyi; Zhu, Siqi; Zhang, Zhenao; Guo, Zihao; An, Jiaqi; Yin, Bowen; Ma, Yuxia (Frontiers in Endocrinology, 2022)
Aims: Sesamin, the main lignin constituent of sesame, plays a pivotal role in regulating physical state. Some studies have evidenced that the supplementation of sesamin may decrease cardiovascular diseases risk. The goal of this systematic review was to summarize evidence of the effects of sesamin supplementation on obesity, blood pressure and lipid profile in humans by performing a meta-analysis of randomized controlled trials. Data Synthesis: Five databases (Pubmed, Cochrane Library, EMBASE, Web of Science and Scopus) were searched electronically from inception to July 30 2021 to identify randomized controlled trials that assessed the impact of sesamin on obesity, blood pressure and lipid profile. Weighted mean difference (WMD) and standard deviation (SD) were used to present the major outcomes. Conclusions: Seven trials (n= 212 participants) were included in the overall analysis. Results showed that sesamin supplementation causing greatly reductions in TC (WMD: -10.893, 95% CI: −19.745 to −2.041, p = 0.016), LDL-c (WMD: -8.429, 95% CI: −16.086 to −0.771, p = 0.031) and SBP (WMD: −3.662, 95% CI: −6.220 to −1.105, p = 0.005). Whereas it had no effect on HDL-c, TG, DBP, nor on weight. Subgroup analysis showed that duration, parallel-designed and unhealthy status can affect TC, LDL-c and SBP evidently. We didn’t discover a strong link between indicators included changes and duration of supplementation. Sesamin can be used as an obtainable dietary supplement to improve blood pressure and blood lipids, and further as a health product to prevent cardiovascular diseases.